Are Transport and Raw Materials Nodes in Global Commodity Chains Potential Places for Worker/Movement Organization?. (28th June 2017) - Sowers, Elizabeth A.; Ciccantell, Paul S.; Smith, David A.
Abstract : Historically, workers exerted power by interrupting long distance flows of commodities at the extraction, processing, and transport stages. Labor, often organized through traditional unions, seized this vulnerability in disparate industries to gain higher wages and better working conditions and to achieve political goals in national and international arenas. However, is this still a viable strategy in a very different era? In this context, what are the opportunities for and constraints on efforts by labor and social movement organizations to take advantage of vulnerabilities in the raw materials and transport nodes of commodity chains? To address these questions, we examine three case studies, including containerized manufactured goods, oil, and coal, in order to understand the matrix of opportunities and constraints confronting labor and social movement organizations in these industries today. In analyzing these critical capitalist commodity chains, we do not focus on individual instantiations of labor organizing in particular places, but instead we provide a wider view of vulnerabilities across large‐scale commodity chains to be harnessed by various actors in struggles for worker justice.